Global Climate Change: An Urgent Call for Collective Action - Tiwari, Jagriti; Upadhyay, Khushboo (Journal of Advanced Research in Alternative Energy, Environment and Ecology; Vol 11 No 3&4 (2024): Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2024)
Global climate change represents one of the most significant challenges facing humanity today, with far-reaching implications for the environment, economies, and social systems. The increasing concentration of greenhouse gases (GHGs) in the atmosphere due to human activities has led to rising global temperatures, extreme weather events, and significant ecological disruptions. According to the Intergovernmental Panel on Climate Change (IPCC), we are on track to exceed a 1.5Â°C increase in global temperatures by the end of the century if current trends continue. This review article synthesizes current research on the causes and effects of climate change, emphasizing the urgent need for comprehensive mitigation and adaptation strategies. We explore the scientific basis of climate change, the role of human activities in exacerbating these changes, and the resulting impacts on biodiversity, food security, and human health. Additionally, we examine potential pathways for reducing emissions, including the transition to renewable energy, enhancing energy efficiency, and implementing carbon sequestration technologies. The article also highlights the importance of adaptive measures to build resilience in vulnerable communities, underscoring the necessity of integrating climate considerations into policymaking.